Effects of initial aquifer conditions on economic benefits from groundwater conservation. Issue 1 (22nd January 2017) - Foster, T.; Brozović, N.; Butler, A. P.
Abstract: Worldwide, there is growing recognition of the need to reduce agricultural groundwater use in response to rapid rates of aquifer depletion. To date, however, few studies have evaluated how benefits of conservation vary along an aquifer's depletion pathway. To address this question, we develop an integrated modeling framework that couples an agro‐economic model of farmers' field‐level irrigation decision‐making with a borehole‐scale groundwater flow model. Unique to this framework is the explicit consideration of the dynamic reductions in well yields that occur as an aquifer is depleted, and how these changes in intraseasonal groundwater supply affect farmers' ability to manage production risks caused by climate variability and, in particular, drought. For an illustrative case study in the High Plains region of the U.S., we apply our model to analyze the value of groundwater conservation activities for different initial aquifer conditions. Our results demonstrate that there is a range of initial conditions for which reducing pumping will have long‐term economic benefits for farmers by slowing reductions in well yields and prolonging the usable lifetime of an aquifer for high‐value irrigated agriculture. In contrast, restrictions on pumping that are applied too early or too late will provide limited welfare benefits. We suggest, therefore, that there are "windows of opportunity" to implement groundwater conservation, which will depend on complex feedbacks between local hydrology, climate, crop growth, and economics. Key Points: Economic value of groundwater conservation depends on initial aquifer conditions Optimal point to limit pumping is a function of local hydrology, climate, and economics Sustaining well yields increases productivity and maintains drought resilience